Organization of Emergency Departments and Changing Patient Profile During COVID-19 Outbreak: A University Hospital Experience in Turkey - Bayram, Başak; Can, İsmail Özgür (The Bulletin of Legal Medicine, 2020)
During the COVID-19 epidemic, emergency departments played an important role in identifying patients, isolating, preventing in-hospital infections, and informing public health authorities. It is necessary to identify the possible patients quickly and isolate them from others. It was necessary to reorganize the emergency departments, which will be the first place of admission for the majority of patients. Emergency patient care should continue in emergency departments even in disasters, and in many countries, emergency departments operate at maximum capacity in their normal routines. For all these reasons, policies are required to prevent crowding in health centers and to control them, especially in emergency departments identify patients before hospital admission if possible. In this study, we explain that how the organization of a university hospital emergency department with the COVID-19 pandemic, and how to organization the infected patients, emergency patients and forensic cases in emergency department.